Professional Doctoral Scholarship in Ghana: A Case Study of the CDT-BEPS Framework. (June 2015) - Owusu-Manu, D.; Edwards, D.J.; Afrane, S.K.; Dontwi, I.K.; Laycock, P.
The constantly evolving paradigm of 21st century educational offerings and the growing demand for 'professional practice' research degrees have raised concerns about the relevance of the traditional 'theoretical' PhD award. To meet this growing demand, and address these concerns, alternative routes to achieving the doctoral award have been developed (such as EngD and DBA). However, many higher education institutions in developing countries have not responded to the new demand. Against this contextual background, this paper reports on a case study of the recently established Centre for Doctoral Training in Business, Enterprise and Professional Studies (CDT-BEPS) at Kwame Nkrumah University of Science and Technology (KNUST), Ghana. The CDT-BEPS embraces five development stages of professional doctoral training and learning skills sets: business; research; creativity; transferability; and evidential learning. The framework for developing the CDT-BEPS was validated using feedback from an international panel of experts encompassing academics, researchers, students and practitioners. It is argued that the research findings may be useful for other HEIs in developing countries currently exploring alternative routes for doctoral training. It is noted that further research is required to establish strategic collaborative and operational frameworks to support the CDT-BEPS and its long-term sustainability.